Ortho-substituted PCB 153: effects in CHO-K1 cells - Miletić Marina; Murati Teuta; Šimić Branimir; Bilandžić Nina; Brozović Anamaria; Kmetič Ivana (Arhiv za Higijenu Rada i Toksikologiju, 2021)
Non-planar di-ortho-substituted PCB 153 (2,2’,4,4’,5,5’-hexachlorobiphenyl), one of the most abundant PCB congeners in the environment and in biological and human tissues, has been identified as potential endocrine disruptor affecting the reproductive and endocrine systems in rodents, wildlife, and humans. The aim of this study was to gain a deeper insight into its mode/mechanism of action in Chinese hamster ovary K1 cells (CHO-K1). PCB 153 (10–100 μmol/L) inhibited CHO-K1 cell proliferation, which was confirmed with four bioassays (Trypan Blue, Neutral Red, Kenacid Blue, and MTT), of which the MTT assay proved the most sensitive. PCB 153 also induced ROS formation in a dose-dependent manner. Apoptosis was seen after 6 h of exposure to PCB 153 doses ≥50 μmol/L, while prolonged exposure resulted in the activation of the necrotic pathway. PCB 153-induced disturbances in normal cell cycle progression were time-dependent, with the most significant effects occurring after 72 h.